The magnetic ordering in high magnetoresistance Mn-doped ZnO thin films - S. Venkatesh; A. Baras; J.-S. Lee; I. S. Roqan (AIP Advances, 2016)
We studied the nature of magnetic ordering in Mn-doped ZnO thin films that exhibited ferromagnetism at 300 K and superparamagnetism at 5 K. We directly inter-related the magnetisation and magnetoresistance by invoking the polaron percolation theory and variable range of hopping conduction below the metal-to-insulator transition. By obtaining a qualitative agreement between these two models, we attribute the ferromagnetism to the s-d exchange-induced spin splitting that was indicated by large positive magnetoresistance (∼40 %). Low temperature superparamagnetism was attributed to the localization of carriers and non-interacting polaron clusters. This analysis can assist in understanding the presence or absence of ferromagnetism in doped/un-doped ZnO.